The Problem of Selective Interpretation in Exegetical Works and Methodological Standards to Limit It - Omran, Ruqaya Abbas; Al-Shammari , Raouf Ahmed (Journal of Ecohumanism, 2025)
This study is concerned with examining the issue of selectivity and its serious effects on interpretive corpora. The authors of these corpora sought, through its application, to achieve certain goals that are characterized by bias and a departure from objectivity. Those who adopt the selective approach tend to choose and select evidence based on prior considerations set by the interpreter to align with their sectarian, doctrinal, or political objectives. This means that the practitioner of the selective approach views the Quranic verses and the surrounding contexts with a one-sided perspective, which leads to a deviation from the intended purpose of the Quranic verses, with their primary concern being to support their own opinion without regard for the divine intent.